Growth of Sputtered Nanocomposite Alloys on Polymeric Substrates: The Role of the Substrate's Mechanical Hardness1. Issue 11 (13th August 2013) - Zuber, Kamil; Downey, Elisabeth; Hall, Colin; Murphy, Peter; Evans, Drew
<x xml:space="preserve">Abstract</x> Thin multilayer structures consisting of a nanocomposite CrZrx alloy on SiO2 are grown by magnetron sputtering onto hard‐coated polymeric substrates at 350 K. The grain structure and electrical, optical, and mechanical properties of the nanocomposite alloy were investigated using atomic force microscopy, dc conductivity, spectrophotometry, and nano‐scratch testing. Despite the sputtered films being grown in the same deposition run, the grain structure and properties of the thin films were observed to change depending on the siloxane‐based hard‐coat employed. These studies indicate that in addition to the substrate's roughness, the hardness of the siloxane‐based hard‐coat correlates well with the changing properties of the sputtered thin films. To rationalize the influence of the substrate hardness, a hypothesis is proposed where the substrate hardness dissipates a portion of the sputtered material's energy upon impact, leading to changes in its residual energy, thus influencing the material's ability to laterally diffuse on the substrate.